AUTISM SPECTRUM DISORDER: THE SITUATION TODAY IN LIBYA – “A PERSPECTIVE” - ADEL M ZEGLAM,; NAJAH S WAHRA, (Innovare Journal of Medical Sciences, 2025)
This perspective is to attract the attention of researchers, policymakers, and healthcare professionals working in the field of autism spectrum disorder (ASD). It aims to describe the ASD situation in Libya with regards to prevalence, attitude toward children with ASD, and challenges facing families in taking care of their children. The prevalence of autism in developing countries is generally lower than in developed countries; however, it is important to note that this may be attributable to underdiagnosis, lack of knowledge, under-reporting, and the associated social stigma rather than true differences in prevalence. In conclusion, inadequate resources, infrastructure, and setup have hampered large-scale epidemiological studies needed to obtain accurate data. There ought to be a need for more widespread and consistent epidemiological studies to obtain accurate and up-to-date prevalence data on ASD in Libya to schedule plans and allocate funds for diagnosis, treatment, and support services. In general, there are no clear policies regarding inclusive education and integration. It is very important that future researches should take into account the cultural, social, and socioeconomic elements that exist in Libya and may wish to use different approaches for data collection.